2008
DOI: 10.1007/s11661-008-9686-z
|View full text |Cite
|
Sign up to set email alerts
|

Creep-Fatigue Interactions in a 9 Pct Cr-1 Pct Mo Martensitic Steel: Part I. Mechanical Test Results

Abstract: Creep-fatigue (CF) tests are carried out on a modified 9 pct Cr-1 pct Mo (P91) steel at 550°C. These CF tests are strain controlled during the cyclic part of the stress-strain hysteresis loop and then load controlled when the stress is maintained at its maximum value, to produce a prescribed value of the creep strain before cyclic deformation is reversed under strain-controlled conditions. The observed cyclic softening implies that the applied creep stress continuously decreases with the number of cycles. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Such tests are reported in the first part of this study. [25] Creep-fatigue tests can thus be used as ''accelerated'' tests. Because the microstructure observed after CF tests is comparable to that observed after several years of in-service conditions (mainly creep loading), testing samples prestrained in CF allows estimation of the actual mechanical properties of the steels after in-service loadings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such tests are reported in the first part of this study. [25] Creep-fatigue tests can thus be used as ''accelerated'' tests. Because the microstructure observed after CF tests is comparable to that observed after several years of in-service conditions (mainly creep loading), testing samples prestrained in CF allows estimation of the actual mechanical properties of the steels after in-service loadings.…”
Section: Discussionmentioning
confidence: 99%
“…[25] B. Observation Techniques Several specimens are observed using different techniques in order to characterize the microstructural evolutions at different scales.…”
Section: A Materials and Mechanical Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since these components will be subjected to high-temperature cyclic loadings, data about creep-fatigue properties are required in design procedures. Recent studies on commercial Grade 91 (''G91" which is a modified 9Cr-1Mo steel) showed that cyclic loadings coupled to high-temperature creep loadings lead to a fast and strong cyclic softening effect, which deteriorates the mechanical properties such as the creep strength [3][4][5][6][7]. This phenomenon was shown to be mainly due to a coarsening of the microstructure, in particular the decrease of the dislocation density, and the coalescence of precipitates.…”
Section: Introductionmentioning
confidence: 99%
“…The value of D c which is specific to the test conditions has been experimentally determined for tensile stress 18 Virgo steel ( (8) where (da/dN) CF is the rate of crack propagation in 'pure fatigue', i.e. without hold time.…”
Section: Modelling Creep-fatigue Interactions In Relation With Intergmentioning
confidence: 99%